2016
DOI: 10.7554/elife.21356
|View full text |Cite
|
Sign up to set email alerts
|

The Chd1 chromatin remodeler shifts hexasomes unidirectionally

Abstract: Despite their canonical two-fold symmetry, nucleosomes in biological contexts are often asymmetric: functionalized with post-translational modifications (PTMs), substituted with histone variants, and even lacking H2A/H2B dimers. Here we show that the Widom 601 nucleosome positioning sequence can produce hexasomes in a specific orientation on DNA, providing a useful tool for interrogating chromatin enzymes and allowing for the generation of nucleosomes with precisely defined asymmetry. Using this methodology, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 80 publications
(127 reference statements)
7
89
0
2
Order By: Relevance
“…The major peak appears at high FRET of 0.9 as expected from the proximity between the Cy3 and Cy5 dyes (Figure 1B, top). A minor mid-FRET peak at 0.6 is likely due to the Cy5-labeled H2A at a distal position as seen in previous studies (Deindl et al, 2013; Levendosky et al, 2016). FRET peaks did not change upon addition of Chd1 protein alone without ATP (Figure 1B, middle).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The major peak appears at high FRET of 0.9 as expected from the proximity between the Cy3 and Cy5 dyes (Figure 1B, top). A minor mid-FRET peak at 0.6 is likely due to the Cy5-labeled H2A at a distal position as seen in previous studies (Deindl et al, 2013; Levendosky et al, 2016). FRET peaks did not change upon addition of Chd1 protein alone without ATP (Figure 1B, middle).…”
Section: Resultssupporting
confidence: 62%
“…Compared to nucleosomes, hexasomes lack one histone H2A/H2B dimer, and we recently demonstrated that Chd1 was unable to robustly shift hexasomes toward the side lacking H2A/H2B (Levendosky et al, 2016). To monitor Chd1 activity on poor hexasome substrates, we produced end-positioned hexasomes with the side lacking the H2A/H2B dimer adjacent to the long flanking DNA, such that the Cy3-labeled DNA end was on the side with the remaining H2A/H2B dimer (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the slower rate for A 16 [SHL2.5/3.5-right] was due to a catalytic or a binding effect, we monitored the kinetics of sliding for 0-N-80 nucleosomes with saturating Chd1 using a fluorescence-quenching assay 31 . In this assay, Dabcyl was attached to the short DNA end of an 0-N-80 nucleosome, which placed it close enough to quench a Cy3B fluorophore attached to histone H2A at T120C.…”
Section: Resultsmentioning
confidence: 99%
“…The 601 is notably asymmetric: one side has a higher affinity for histones than the other, and the strength of histone-DNA are unevenly distributed, with strongest contacts near the dyad 31, 43, 44 . The central portion of 601 is also asymmetric with respect to periodic TA steps, with one side of the dyad having a TA step at four consecutive turns of DNA where the minor groove faces the histone core, whereas the other side possesses just a single TA step (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation